Effective talent development: the elite coach perspective in UK sport - Martindale, R. J. J.; Collins, D.; Abraham, A. (Journal of Applied Sport Psychology, 2007)
Research to effectively inform the design and conduct of talent development environments (TDEs) is sparse, especially relating to the goals and systems involved. Accordingly, this paper provides a detailed picture of effective goals and systems within TDEs in a UK context. A thorough examination of the goals, nature and systems of 16 coaches with significant expertise in talent development was carried out across 13 different sports. Inductive and deductive analysis revealed support for 5 main generic characteristics of effective TDEs: 1) Long-term aims and methods; 2) Wide-ranging coherent messages and support; 3) Emphasis on appropriate development not early success; 4) Individualized and ongoing development; and 5) Integrated, holistic and systematic development. Implications for applied practitioners, policy makers and researchers are explored.